The Invisible Story: Underground Health Narratives of Women in Mining - Mutendi, Mutsawashe (Social Anthropology, 2019)
This dissertation may be read on several different levels. At its most accessible, it is a detailed ethnographic description of how ‘women in mining’ negotiate the daily terrain of caregiving and being exposed to highly contagious and resistant diseases that are associated with mining, which could potentially adversely affect their day-to-day lives, wellbeing and family relations. At its most analytical, it utilises Nixon’s concept of ‘slow violence’ by carefully charting the challenges that a female mineworker faces; having to provide for her family even in the most difficult situations, and sometimes at the expense of her own health. Hence, ‘women in mining’ are situated in a web of connections that exist between working underground and being caregivers in their homes; while at risk of transmitting tuberculosis (TB) and acquiring reproductive health related problems. This dissertation illustrates the tactics and coping strategies that women in mining employ, and argues that they ‘make a plan’ to minimise the negative social consequences of ill health.